2021
DOI: 10.1021/acsami.1c14335
|View full text |Cite
|
Sign up to set email alerts
|

High Breakdown Current Density in Quasi-1D van der Waals Layered Material Ta2NiSe7

Abstract: We synthesized ternary composition chalcogenide Ta 2 NiSe 7 , a quasi-one-dimensional (Q1D) material with excellent crystallinity. To utilize the excellent electrical conductivity property of Ta 2 NiSe 7 , the breakdown current density (J BD ) according to thickness change through mechanical exfoliation was measured. It was confirmed that as the thickness decreased, the maximum breakdown voltage (V BD ) increased, and at 18 nm thickness, 35 MA cm −2 of J BD was measured, which was 35 times higher than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The compositional differences between the three points suggest that severe damage to the crystal structure of PtSe 2 is caused by the large amount of Joule heat during the breakdown. Se, as one of the chalcogens, is unstable due to surface oxidation, making it prone to form atomic pairs with oxygen, which is easy to desorb from the material surface. , We have demonstrated the presence of Se–O pairs on the surface of PtSe 2 by an X-ray photoelectron spectrum (XPS), which indicates the pairing of Se with O will create Se vacancies on the PtSe 2 surface and has potential for defect-induced electromigration . For the final discussion, we have determined the TBC of the PtSe 2 /SiO 2 interface and verified the threshold operating state of multilayer PtSe 2 devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compositional differences between the three points suggest that severe damage to the crystal structure of PtSe 2 is caused by the large amount of Joule heat during the breakdown. Se, as one of the chalcogens, is unstable due to surface oxidation, making it prone to form atomic pairs with oxygen, which is easy to desorb from the material surface. , We have demonstrated the presence of Se–O pairs on the surface of PtSe 2 by an X-ray photoelectron spectrum (XPS), which indicates the pairing of Se with O will create Se vacancies on the PtSe 2 surface and has potential for defect-induced electromigration . For the final discussion, we have determined the TBC of the PtSe 2 /SiO 2 interface and verified the threshold operating state of multilayer PtSe 2 devices.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 We have demonstrated the presence of Se−O pairs on the surface of PtSe 2 by an X-ray photoelectron spectrum (XPS), which indicates the pairing of Se with O will create Se vacancies on the PtSe 2 surface and has potential for defect-induced electromigration. 48 Material Characterization. Multilayer PtSe 2 flakes were identified by optical microscopy (LV100D, Nikon, Japan).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In terms of the dimension of nanomaterials, research on a wire-shaped quasione-dimensional (Q1D) van der Waals (vdW) material with further reduced dimensions from a 2D structure has been studied continuously with high current-carrying characteristics. [22][23][24][25] Balandin et al reported that Q1D materials could be applied further to sensor, optoelectronic, and quantum technologies and observed high performance as an interconnect. [26] Therefore, going beyond the 2D material research category, this study focused on synthesizing noble metal containing Q1D metallic nanowires with high current capacity.…”
Section: Doi: 101002/smll202205344mentioning
confidence: 99%
“…To fulfill these demands, low-dimensional van der Waals (vdW) materials, such as transition-metal dichalcogenides (TMDCs), have been extensively explored as next-generation semiconducting channel materials due to their unique structure and multifunctional characteristics. However, it becomes ultimately necessary to consider the use of one-dimensional (1D) vdW materials that have been scaled down even further in size than two-dimensional vdW materials, as they offer the potential for even greater scale-down in nanotechnology. , One-dimensional vdW materials could show remarkable electrical properties thanks to the presence of multiple molecular wires held together by weak vdW interaction. , This distinctive arrangement of 1D vdW materials plays a significant role in the creation of high-quality surfaces without dangling bonds, thereby enabling separation down to the nanometer scale while minimizing surface defects. Therefore, they could suggest the potential for superior electrical characteristics per unit area such as achieving high current capacity , and high carrier mobility , at the nanometer scale without the need for complicated treatment processes. When compared with other low-dimensional materials, 0D structured materials lack stability when composed of combinations in the form of a single atomic unit.…”
Section: Introductionmentioning
confidence: 99%